Bad Faith Tokoh Yakushi Kabuto dalam Manga Naruto Shippuden Karya Masashi Kishimoto: Kajian Eksistensialisme Jean-Paul Sartre: Yakushi Kabuto's Bad Faith in Masashi Kishimoto's Naruto Shippuden Manga: A Study of Jean-Paul Sartre's Existentialism - Narendra Pinasthika; Syihabbudin (Jurnal Pendidikan Bahasa Jepang Undiksha, 2026)
This study aims to analyze the representation of bad faith in the character Yakushi Kabuto in Masashi Kishimoto's Naruto Shippuden manga using Jean-Paul Sartre's existentialism approach. This study uses a qualitative approach with a descriptive-analytical method, with the main data source being manga texts that display Kabuto's inner conflict and character development, and supported by Sartre's existentialism theoretical study. The results of the analysis show that bad faith in Kabuto's character is formed gradually through the denial of existential freedom, self-reduction as a social tool or function, and dependence on identity determination by others, which places him in a being-for-others position and triggers an existential crisis. The Izanami technique is understood as a philosophical turning point that breaks the cycle of bad faith by forcing Kabuto to face himself reflectively without external roles and justifications, so that he returns to being a conscious subject who recognizes his existential freedom and responsibility. Thus, the character Yakushi Kabuto in the Naruto Shippuden manga represents a profound philosophical reflection on the formation of human identity, freedom, and existential crisis.